Instruction Fine-Tuning on Multi-Turn Safety Dialogues Enhances Robustness Without Compromising HumanEval Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: Can instruction fine-tuning on multi-turn safety dialogues improve robustness against code decomposition attacks without degrading HumanEval pass@1 scores. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 1.5/10. This report is a machine-generated literature synthesis
Machine-generated literature synthesis.